Protection and antibody response induced by intramuscular DNA vaccine encoding for viral haemorrhagic septicaemia virus (VHSV) G glycoprotein in turbot (Scophthalmus maximus) - Pereiro, Patricia; Martínez-López, Alicia; Falcó, Alberto; Dios, S.; Figueras Huerta, Antonio; Coll, Julio; Novoa, Beatriz; Estepa, Amparo (Fish & Shellfish Immunology, 2012)
7 páginas, 5 figuras Turbot (Scophthalmus maximus) is a high-value farmed marine flatfish with growing demand and production levels in Europe susceptible to turbot-specific viral haemorrhagic septicaemia virus (VHSV) strains. To evaluate the possibility of controlling the outbreaks of this infectious disease by means of DNA vaccination, the gpG of a VHSV isolated from farmed turbot (VHSV860) was cloned into an expression plasmid containing the human cytomegalovirus (CMV) promoter (pMCV1.4-G860). In our experimental conditions, DNA immunised turbots were more than 85% protected against VHSV860 lethal challenge and showed both VHSV-gpG specific and neutralizing antibodies. To our knowledge this is the first report showing the efficacy of turbot genetic immunisation against a VHSV. Work is in progress to determine the contribution of innate and adaptive immunity to the protective response elicited by the immunization. This work was supported by the projects Consolider Ingenio 2010, CSD2007-00002 and AGL2011-28921-C03 both from the Spanish Ministerio de Ciencia e Innovación (MICINN). Peer reviewed